Redesigning Bramante's rounded perspective: digital speculations on the unbuilt cloister of the Tempietto - Nicola D'Addario; Carla Garrido de Oliveira (Virtual Archaeology Review)
This study explores the speculative digital reconstruction of an unrealized circular cloister designed by Donato Bramante as part of his project for the Tempietto of San Pietro in Montorio, Rome, circa 1502–1510. By referencing Sebastiano Serlio’s surviving drawing—the only contemporary representation of this project—and employing 3D digital modeling, the study examines two potential configurations for the cloister, shedding light on Bramante’s integration of Vitruvian principles into Renaissance architectural theory. The research highlights the challenges posed by the Tempietto’s unique spatial constraints, as well as the role of classical architectural archetypes, particularly the paradigm of the column and architrave in classical designs. Documenting the reconstruction process, this study applies digital reconstruction methodologies, including the Apollonio-Fallavollita-Foschi uncertainty scale, to explore the architectural and structural solutions and the references Bramante might have considered. By addressing whether an architrave- or arch-based system might have been proposed, the research provides insights into Bramante’s architectural intent. This analysis emphasizes the potential of digital reconstructions in addressing historical designs characterized by high levels of uncertainty and interpreting lost architectural works. As part of the international CoVHer Project, this research demonstrates the value of digital tools in cultural heritage preservation and their potential to reinterpret lost or unrealized architectural works. These findings enrich the historiography of architecture, offering new approaches to verifying and reimagining historical designs. Future studies could extend these methodologies to explore other speculative reconstructions, bridging historical inquiry with contemporary visualization techniques.